2003
DOI: 10.1023/b:appa.0000006541.68245.94
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clofentezine on Life-table Parameters in Two-spotted Spider Mite Tetranychus urticae

Abstract: Sublethal effects of the growth inhibitor, clofentezine, on life-table parameters of Tetranychus urticae Koch females treated at different developmental stages with a concentration causing >90% mortality were investigated. Females which survived treatment as 'early' (0-24 h old) eggs produced 12% more offspring than the untreated females during the first five days of oviposition. This resulted in a significant rise in the intrinsic rate of increase (rj): 0.324, compared to 0.299 in the untreated females. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 5 publications
7
25
0
1
Order By: Relevance
“…On the other hand, our previous life-table assays with the growth inhibitor clofentezine revealed that this acaricide decreased both the longevity and fertility of two-spotted spider mite females surviving treatment as larvae, protonymphs or deutonymphs, but no effect was found on the developmental time. Similar effects have been observed for flufenzine, another tetrazine growth inhibitor (Marcic 2002(Marcic , 2003. Jackknife estimate values within each parameter followed by different letters differ based on 95% CLs.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…On the other hand, our previous life-table assays with the growth inhibitor clofentezine revealed that this acaricide decreased both the longevity and fertility of two-spotted spider mite females surviving treatment as larvae, protonymphs or deutonymphs, but no effect was found on the developmental time. Similar effects have been observed for flufenzine, another tetrazine growth inhibitor (Marcic 2002(Marcic , 2003. Jackknife estimate values within each parameter followed by different letters differ based on 95% CLs.…”
Section: Discussionsupporting
confidence: 63%
“…The leaf discs containing eggs, or immatures (larvae, protonymphs or deutonymphs) that developed from the eggs, were sprayed by thin-layer chromatography sprayer with the amount of 0.5-0.6 ml liquid per replication (2-2.5 mg deposite/cm 2 ) (Anonymous 1990;Marcic 2003). The concentrations of tebufenpyrad (in mg/l a.i.)…”
Section: Life-table Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The population growth parameters of T. urticae such as developmental rate, survival, reproduction and longevity can vary in particular with respect to temperature, host plant species, host plant nutrition, cultivar kind, phenological stage, exposure to pesticides, relative humidity, etc. (Sabelis 1981;Brandenburg and Kennedy 1987;Wermelinger et al 1991;Wilson 1994;Dicke 2000;James and Price 2002;Marcic 2003;Skorupska 2004;Ahmadi et al 2006). Accordingly, the majority of management tactics for the two-spotted spider mite rely upon applying acaricides by producers while repeated treatments are necessary to prevent or control outbreaks of T. urticae but likely impact natural enemies via lethal and/or sublethal effects (Croft 1990;Desneux et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using demographic techniques to quantify sublethal effects of pesticides on spider mites have been reported (Boykin and Campbell 1982;Ahmadi 1983;Jones and Parrella 1984;Ibrahim and Knowles 1986;Stark et al 1997;Marcic 2003) but none have considered azadirachtin. Therefore, we evaluated the effects of this compound against adult T. urticae, using demographic toxicological analysis and speculate the possibility of incorporating azadirachtin in the management of the two-spotted spider mite.…”
Section: Introductionmentioning
confidence: 99%